Dual response audiometry: a time-saving technique for enhanced objective auditory assessment - Hoth, Sebastian; Lochmann, Holger Peer (International journal of audiology, 1999)
The effectiveness of objective audiometric assessment can be improved by simultaneously recording transient evoked otoacoustic emissions (TEOAE) and auditory brainstem responses (ABR). Using a stimulation paradigm based on sequences of linearly balanced click stimuli (as described by Kemp et al.1) acoustical and electrical responses of the auditory system can be obtained in one single run (dual response audiometry, DRA). The click stimuli are presented via an ear canal probe containing a speaker and a miniature microphone. EEG activity is recorded from surface electrodes fixed at the vertex and the mastoid ipsilateral to stimulus presentation. Microphone output and voltage difference between electrodes are fed into a dual-channel data acquisition system, where they are separately amplified and filtered into appropriate frequency ranges. After each stimulus, sweeps of 256 samples within a time window of 17 ms are taken of both signals. They are subject to artefact rejection and averaging of amplitude and polarity. The electrical responses to low and high level clicks within one stimulus sequence are processed separately, whereas the acoustical responses are summated across levels in order to eliminate stimulus-related contamination. As the result of one single run, ABR at two levels and non-linear TEOAEs are obtained within approximately 1 min. The signal quality is estimated by correlation analysis and binomial statistics. Among various features of DRA, the most important advantage is the improvement of the success rate. The influence of perturbations is limited since muscle artefacts due to motor activity affect only the ABR, whereas noise contamination affects only the TEOAE. The accuracy of threshold determination is better than with conventional ABR since the stimulus level is measured in situ. One DRA examination provides complete information about the functional integrity of the cochlea and neural pathways without additional time. It appears ideal for the application as a second stage infant screen.
Elektronische Reproduktion der Druck-Ausgabe
Gesehen am 25.02.2021